Complete Genome Sequence of Spiroplasma apis B31(T) (ATCC 33834), a Bacterium Associated with May Disease of Honeybees (Apis mellifera) - Ku, Chuan (American Society for Microbiology, 2014)
Spiroplasma apis B31(T) (ATCC 33834) is a wall-less bacterium in the class Mollicutes that has been linked to May disease of honeybees (Apis mellifera). Here, we report the complete genome sequence of this bacterium to facilitate the investigation of its virulence factors.